2022
DOI: 10.1159/000521704
|View full text |Cite
|
Sign up to set email alerts
|

Developmental Iron Deficiency Dysregulates TET Activity and DNA Hydroxymethylation in the Rat Hippocampus and Cerebellum

Abstract: Iron deficiency (ID) during neurodevelopment is associated with lasting cognitive and socioemotional deficits, and increased risk for neuropsychiatric disease throughout the lifespan. These neurophenotypical changes are underlain by gene dysregulation in the brain that outlasts the period of ID; however, the mechanisms by which ID establishes and maintains gene expression changes are incompletely understood. The epigenetic modification 5-hydroxymethylcytosine (5hmC), or DNA hydroxymethylation, is one candidate… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
9
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 10 publications
(10 citation statements)
references
References 39 publications
1
9
0
Order By: Relevance
“…With specific areas of impairment connected to brain regions that appeared to be most negatively impacted by iron deficiency, including myelination and the hippocampus. neonatal iron deficiency has been repeatedly linked to inferior neurodevelopmental outcomes overall ( 31 33 ). It is particularly important to ensure adequate brain iron status in the neonatal period because, specifically for infants, brain iron deficiency develops more rapidly when there is a lack of iron, and the developmental disruptions brought on by the lack of iron are not reversed by later repletion ( 34 ).…”
Section: Discussionmentioning
confidence: 99%
“…With specific areas of impairment connected to brain regions that appeared to be most negatively impacted by iron deficiency, including myelination and the hippocampus. neonatal iron deficiency has been repeatedly linked to inferior neurodevelopmental outcomes overall ( 31 33 ). It is particularly important to ensure adequate brain iron status in the neonatal period because, specifically for infants, brain iron deficiency develops more rapidly when there is a lack of iron, and the developmental disruptions brought on by the lack of iron are not reversed by later repletion ( 34 ).…”
Section: Discussionmentioning
confidence: 99%
“…38 Iron-deficient diets during neurodevelopment result in decreased TET activity and reduced global hydroxymethylation in rat brain. 39 Apart from the reaction substrates, it was found that vitamin C enhances the abundance of ox-mC in various cell cultures, from iPSCs and ESCs to cancer cell lines and also activates histone demethylation by Jhdm. 40 Although it was originally prescribed a role in maintaining iron in the reduced form Fe( ii ), no other reducing agents were found to exert similar stimulation of the oxygenase activity.…”
Section: Reversal Of Genomic Cytosine-5 Methylationmentioning
confidence: 99%
“…While these long-term epigenetic changes were found in the hippocampus, a focus of our study, they could also occur in the cerebral cortex and cerebellum as these brain structures have a long developmentally-sensitive window [ 57 ]. Future studies could investigate the epigenomic effects of early-life ID on other developing brain regions as we have in a previous study [ 58 ].…”
Section: Discusionmentioning
confidence: 99%